On the estimation of distance distribution functions for point processes and random sets - Stoyan, Dietrich (Image analysis and stereology, 2001)
This paper discusses various estimators for the nearest neighbour distance distribution function D of a stationary point process and for the quadratic contact distribution function Hq of a stationary random closed set. It recommends the use of Hanisch's estimator of D, which is of Horvitz-Thompson type, and the minussampling estimator of Hq. This recommendation is based on simulations for Poisson processes and Boolean models.
Keywords: Image Processing, Computer-Assisted; Poissonova distribucija; Random Allocation; Slika, obdelava z računalnikom; Slučajnost, razporeditev; Poisson Distribution; razporeditev; obdelava slik